Why Presidential Speech Locations Matter Analyzing Speechmaking from Truman to Obama - O'Brien, Shannon Bow (The Evolving American Presidency, 2018)
This book explores speeches by American presidents. Domestic public presidential speechmaking helps us understand the pressures, priorities, and targeted audiences of different presidencies. Many administrations generally work to reinforce already existing support though some may try to reach out to new areas. Census areas help us better understand where presidents prioritize speeches in certain areas of the country. Designated Market Areas, or media markets, allow us to look at presidential speechmaking without geographical constraints and focus on areas of population concentrations. Electoral College results show that most administrations prefer to give speeches in places where they have the most electoral support to reinforce their bases. The chapter on vacation locations explores how some presidents use Camp David or their homes as places to actively speak, while some administrations just use them as retreats. Foreign speeches allow us to see that most presidents prefer to speak in openly free countries more than other places.